The Influence of Product Quality, Product Innovation on Customer Relationship Management through Prices (Case Study at Creative Industry Payung Geulis in Kahuripan, Indihiang, Tasikmalaya - R. Adjeng Mariana Febrianti; Mariana Rachmawati; Zulganef Zulganef; Sri Astuti Pratminingsih (Dinasti Publisher, 2024)
This research aims to determine the influence of product quality and innovation on customer relationship management through prices in Payung Geulis creative industry in Kahuripan village, Indihiang, Tasikmalaya. This research implies an explanatory survey design using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) as the analysis method. Data collection was carried out through questionnaires distributed to 200 customers. The findings reveal that product quality and innovation significantly influence prices and impact customer relationship management—higher product quality results in greater customer satisfaction and emotional attachment to the price. Additionally, innovation has a positive impact on customer engagement and strengthens the relationship with price. Moreover, price significantly influences customer relationship management, since price reduces resistance to changes in product quality and innovation in customer relationship management. Furthermore, this research shows that the impact of product quality and innovation influences customer relationship management indirectly through price.